Constrictive Pericarditis: A Challenging Diagnosis in Paediatrics - Mariana Faustino; Inês Carmo Mendes; Rui Anjos (Case Reports in Cardiology)
Constrictive pericarditis is an uncommon disease in children, usually difficult to diagnose. We present the case of a 14-year-old boy with a previous history of tuberculosis and right heart failure, in whom constrictive pericarditis was diagnosed. The case highlights the need to integrate all information, including clinical data, noninvasive cardiac imaging, and even invasive hemodynamic evaluation when required, in order to establish the correct diagnosis and proceed to surgical treatment.